The effects of context awareness on the adoption of sports technologies - Öç, Yusuf. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
There is a new era of technology as a result of advancements in artificial intelligence and microsensors. Instant use of contextual data improves service customization with highly personalized feedbacks and objectives. Existing sports literature regarding sports technologies mostly aim to understand the relationship between sports technologies and sports motivation while, on the other hand, marketing and information systems literature try to explain adoption and diffusion of sports technologies with the existing frameworks. In an attempt to extend the current understanding of the intentions of using a context-aware technology from the consumer perspective, we used sports technologies as the study domain and created a new construct, named "Context Awareness," with four dimensions: tracking, coaching, sharing, and gamification. We created 16 scale items to measure the context awareness capabilities to enhance the understanding of usage drivers behind sports technologies. The purpose of this study is to understand the effects of context aware characteristics on users’ adoption together with sports motivation, sports type, and other innovation characteristics. The proposed model is empirically tested with data from 600 participants in Turkey. Partial least squares (PLS) were used for models and hypotheses testing. Context awareness is found to affect perceived innovation characteristics significantly. It is also shown that sports motivation and sports type moderates the relationships in the model.
Keywords: Awareness.; Sports -- Technological innovations.